On the determinants of electron transfer reorganization energy in a cytochrome P450: cytochrome b5 complex: A combined quantum mechanics and molecular dynamics simulation study - Teuffel, Jonathan; Mukherjee, Goutam; Han, Sungho Bosco; Elstner, Marcus; Wade, Rebecca C. (The journal of chemical physics, 2025)
The electron transfer steps in the catalytic cycle of cytochrome P450 (CYP) enzymes, ubiquitous proteins with key roles in processes such as drug metabolism and steroidogenesis, are often rate-limiting. To predict ET rates from atomistic molecular dynamics simulations using Marcus theory, values of the reaction free energy ΔG0 and the reorganization free energy λ are required from either experiments or computations. For the reduction of cytochrome P450 17A1 (CYP17A1) by the secondary redox protein cytochrome b5 (CYb5), a critical step in the regulation of steroidogenesis, experimental measurements of λ are not available. We here describe the computation of λ for this system from a combination of molecular mechanics/molecular dynamics simulations and quantum mechanics computations. Our results show that a quantum mechanical treatment of the redox-active cofactors is necessary, even though the surrounding protein and solvent, which are modeled classically, contribute most to the reorganization energy. The values of λ computed for structural ensembles corresponding to two predicted binding modes of the proteins are 1.23 and 1.16 eV. We find that the λ values computed for the individual soluble globular domains of the two proteins sum to approximately the λ values computed for the membrane-bound CYP17A1-CYb5 complex, indicating that additivity can be invoked in a computationally efficient approach to estimating λ values for such protein-protein complexes.